Integrate the differential equation
Not what you're looking for? Search our solutions OR ask your own Custom question.
This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!
(x^2 + 3y^2) dx - 2xydy = 0
Integrate the differential equation. Complete step by step work must be shown and reduced into lowest terms.
(x^2 + 3y^2)dx = 2xydy
Put, y = vx
=> dy = vdx + xdv
Hence, equation becomes,
(x^2 + 3x^2v^2)dx = 2x.v.x(vdx + xdv)
=> (x^2 + 3x^2v^2)dx = 2x^2v^2dx + 2x^3vdv
=> (x^2 + ...
This shows how to integrate a given differential equation.